Оцінювання оснащеності бурових доліт - Волобуєв, А.І.; Коцкулич, Я.С.; Слепко, М.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
It is offered the estimation procedure of drill bits cutting structure with a help of determination
their “specific equipment”. This procedure may be used for estimation of already existing drilling
bits and while their designing. In first case it gives possibility to determine poor zone in future
where we may expect irregular abrasion. In second case – we can create drilling bits with uniform
distribution specific equipment by radius. It may be useful for specialists that are working in the
area of creating and exploitation drilling bits.